化简:(1)tanx(cosx-sinx)+(sinx+tanx)/(cotx+cscx) (2)sin^2xtanx+cos^2xcotx+2sinxcosx

来源:学生作业帮助网 编辑:作业帮 时间:2018/11/22 18:26:03
化简:(1)tanx(cosx-sinx)+(sinx+tanx)/(cotx+cscx)(2)sin^2xtanx+cos^2xcotx+2sinxcosx化简:(1)tanx(cosx-sinx)

化简:(1)tanx(cosx-sinx)+(sinx+tanx)/(cotx+cscx) (2)sin^2xtanx+cos^2xcotx+2sinxcosx
化简:(1)tanx(cosx-sinx)+(sinx+tanx)/(cotx+cscx) (2)sin^2xtanx+cos^2xcotx+2sinxcosx

化简:(1)tanx(cosx-sinx)+(sinx+tanx)/(cotx+cscx) (2)sin^2xtanx+cos^2xcotx+2sinxcosx
(1)tanx(cosx-sinx)+(sinx+tanx)/(cotx+cscx)
=(sinx-sin²x/cosx)+(sinx+sinx/cosx)/(cosx/sinx+1/sinx)
=(sinx-sin²x/cosx)+sin²x/cosx
=sinx
(2)sin²xtanx+cos²xcot+2sinxcosx
=sin³x/cosx+cos³x/sinx+2sinxcosx
=(sin^4x+cos^4x+2sin²xcos²x)/sinxcosx
=(sin²x+cos²x)²/sinxcosx
=2/sin2x
=2csc2x

1. tanx(cosx-sinx)+(sinx+tanx)/(cotx+cscx)
= sinx - tans sinx + tanx (cosx+1) / [ cosx+1)/sinx]
= sinx - tans sinx + tans sinx = sinx
2. (sinx)^2 tanx+ (cosx)^2 cotx + 2sinxcosx
= (sinx)^2 tanx + sinxcosx + (cosx)^2 cotx + sinxcosx
= tanx + cotx